The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1002/slct.201600048
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Oxidation of NIR Photosensitizers in the Presence of Radical Initiators and Their Prospective Use in Dental Applications

Abstract: Photochemical oxidation of near infrared (NIR) photosensitizers in the presence of diaryl iodonium salts bearing either bis(trifluoromethylsulfonyl)imide or hexafluorophosphate was investigated by exposure with NIR LEDs emitting either at 790 nm, 830 nm, 850 nm or 870 nm. Four different cyanines with barbituryl group at the meso position exhibit similar absorption in the NIR. These photosensitizers initiate in combination with diaryliodonium salts radical photopolymerization of dental composites with the focus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
105
0
14

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 66 publications
(120 citation statements)
references
References 32 publications
1
105
0
14
Order By: Relevance
“…9. The fast decomposition of this species forms also the boundary conditions to reduce the efficiency of electron back transfer in NIR systems as previously shown for Sens1 [21].…”
Section: Mechanism and Selection Of Componentsmentioning
confidence: 58%
See 1 more Smart Citation
“…9. The fast decomposition of this species forms also the boundary conditions to reduce the efficiency of electron back transfer in NIR systems as previously shown for Sens1 [21].…”
Section: Mechanism and Selection Of Componentsmentioning
confidence: 58%
“…The differences obtained for the iodonium salts were not so significant in comparison with the NIR system. From this point of view, the NIR system needs to exhibit a lower yield because the photoproducts formed possess a higher nucleophilicity and possess therefore a high affinity to add the cations formed [8,21]. This explains the lower yield on cations formed.…”
Section: Radical Photopolymerization With Nir and Uv-ledsmentioning
confidence: 99%
“…Highly light sensitive materials are needed for such procedures because the time frame to expose one pixel covers only several s/pixel. Nowadays, some feasibility studies successfully showed the working principle of NIR initiated photopolymerization for coatings [3][4][5][6][7]. The majority of radiation curing relies on the well established UV-curing [8].…”
Section: Introductionmentioning
confidence: 99%
“…One reason can be seen in insufficient solubility of the initiator components Sens and RI in the high viscous resins. Many NIR absorbers based on cyanines and radical initiators based on iodonium salts possess an insufficient solubility in common industrial coatings [3][4][5][6]. There is a need for materials exhibiting an improved solubility in such surroundings either.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation